Flexible Nanoarchitectonics for Biosensing and Physiological Monitoring Applications (Small 9/2023). Issue 9 (1st March 2023) - Ashok, Aditya; Nguyen, Tuan‐Khoa; Barton, Matthew; Leitch, Michael; Masud, Mostafa Kamal; Park, Hyeongyu; Truong, Thanh‐An; Kaneti, Yusuf Valentino; Ta, Hang Thu; Li, Xiaopeng; Liang, Kang; Do, Thanh Nho; et al.
Abstract : Flexible Mesoporous Electronics In article number 2204946, Hoang‐Phuong Phan, Yusuke Yamauchi, Tuan‐Khoa Nguyen, Mostafa Kamal Masud, and co‐workers develop flexible mesoporous architectures using selective electrochemical deposition. Soft metallic nanopores formed on thin polyimide films offer excellent mechanical bendability, high sensitivity for glucose sensing, and low impedance that facilitates detection of neural activities. These features suggest the promise of soft mesoporous material systems for biomedical applications.